Message Encryption in Digital Images using the Zhang LSB Imange Method - Saepulrohman, Asep; Ismangil, Agus; Heliawati, Leny (Ilmu Komputer, FMIPA, Universitas Pakuan, 2024)
Message encryption in digital images using the Zhang LSB Image method is a steganography technique that utilizes the Least Significant Bit (LSB) method to hide secret messages in the last bit of the image pixel. This method allows the use of images as a medium to convey hidden messages. The encryption process involves two main stages, namely message encryption and message hiding in an image. Message encryption is carried out using strong cryptographic algorithms to secure the authenticity and confidentiality of messages. Then, the encrypted message is inserted into the last bit of the image pixel using the LSB method. This is done by modifying the last bit value of the pixel so that the change is not visually visible to the human eye. To recover the original message, the message recovery process involves extracting the last bit of the modified image pixel and decrypting the message using the appropriate key. The Zhang LSB Image method is a steganography technique that is relatively simple but effective in hiding messages in digital images.